Traditional Chinese Medicine: A Class of Potentially Reliable Epigenetic Drugs - Zhu, Daoqi; Li, Aiwu; Lv, Ying; Fan, Qin (Frontiers in Pharmacology, 2022)
Epigenetic modification, especially DNA methylation, plays a nonnegligible role in the occurrence and development of tumors. Increasing studies are indicating that traditional Chinese medicine (TCM) plays a considerable anti-tumor role by regulating the process of DNA methylation modification. Studies on TCM regulating DNA methylation modification mostly focus on the whole genome and abnormal methylation status by active ingredients or single compounds and Chinese herb formula (CHF). The balance and overall concept of TCM theory coincides with the balance of DNA methylation modification in the tumor environment. Regardless of how TCM modulates epigenetics in tumor, it has been shown to bet a class of potentially reliable epigenetic drug.